Citizenship Education in Primary Schools: How Citizenship Conceptions Shape Learning Aims and Classroom Practices - Prince Clinton Immanuel Christian Damanik (PT Bukuloka Literasi Bangsa, 2026)
Citizenship education is foundational to primary school, where young learners begin developing civic identity, values, and participation skills. This paper explores how different conceptions of citizenship influence the aims, curriculum content, and teaching methods in primary school civic education. Using a narrative literature review of peer-reviewed studies published between 2017 and 2024, the analysis examines five citizenship models: liberal, republican, deliberative, global, and Pancasila-based, and their pedagogical implications for elementary learners aged 6 to 12 years. The findings demonstrate that each citizenship conception emphasizes distinct learning objectives. Liberal models prioritize critical thinking and understanding rights; republican frameworks promote cooperative learning and community service; deliberative approaches develop dialogue and empathy; global citizenship cultivates intercultural awareness and environmental responsibility; and Pancasila-based education integrates moral character, national identity, and democratic values through culturally grounded activities. The review reveals that primary school citizenship education functions not merely as knowledge transmission but as a formative process shaping how children understand themselves as members of their communities, nations, and the wider world. In the Indonesian context, Pancasila provides a philosophical and ethical foundation that enables primary school teachers to connect universal civic principles with local cultural values and children's lived experiences. The paper proposes an integrative model of primary school citizenship education that synthesizes these five perspectives, demonstrating how teachers can simultaneously develop children's critical thinking, participation skills, moral reasoning, cultural identity, and global awareness through age-appropriate and contextually relevant pedagogies. Keywords: citizenship education, primary school, Pancasila, global citizenship